Proceedings of the 2017 11th Joint Meeting on Foundations of Software Engineering 2017
DOI: 10.1145/3106237.3106257
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting unsupervised learning for defect prediction

Abstract: Collecting quality data from so ware projects can be time-consuming and expensive. Hence, some researchers explore "unsupervised" approaches to quality prediction that does not require labelled data. An alternate technique is to use "supervised" approaches that learn models from project data labelled with, say, "defective" or "notdefective". Most researchers use these supervised models since, it is argued, they can exploit more knowledge of the projects.At FSE'16, Yang et al. reported startling results where u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 55 publications
1
79
0
Order By: Relevance
“…eir study showed that CCUM performs better than the state-of-the-art prediction model at that time. As the results Yang et al [8] reported are startling, Fu et al [28] repeated their experiment.…”
Section: Effort-aware Software Defect Predictionmentioning
confidence: 91%
“…eir study showed that CCUM performs better than the state-of-the-art prediction model at that time. As the results Yang et al [8] reported are startling, Fu et al [28] repeated their experiment.…”
Section: Effort-aware Software Defect Predictionmentioning
confidence: 91%
“…at el. [2] have reported that supervised predictors did not perform outstandingly better than unsupervised ones for effort-aware just-in-time defect prediction on the basis of their experiments. Recently, Yang et al have proposed an unsupervised model and applied it to projects with rich historical bug data.…”
Section: Background and Related Workmentioning
confidence: 98%
“…Then, they attempted to combine complexity metrics with more metrics such as code churn metrics and token frequency metrics [26,31,43,47,48,52,54,54,57,58,58,65,79,81]. Then, advances have been made to use unsupervised machine learning to predict bugs [25,32,36,46,75,76,77,78,80] using the similar set of complexity metrics. These approaches use the similar metrics as those in bug prediction, but do not capture the difference between vulnerable code and buggy code, which hinders the effectiveness.…”
Section: Related Workmentioning
confidence: 99%